Analisis Harga Air untuk Irigasi Padi Sawah di Wilayah Perkotaan (Kasus Subak Pakel I dan Subak Pagutan Kota Denpasar) - ADITYA, PUTU ANGGA; SUDARMA, I MADE; DJELANTIK, AAA WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2013)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT Water Value Analysis for Rice Irrigation in Urban Areas (Case Study of Subak Pakel I a nd Subak Pagutan Denpasar City) This study is analyzing the real price of water that must be spend by the rice farmer, the contribution of water for rice production by it coefficient elasticity and irrigation trouble that facing the rice farmer in city area, specifically in Denpasar city Bali province. This study uses the regression method and value of marginal product method to reach the water contribution by coefficient elasticity value and the water price. The result of study shows that water contribution to the rice production by coefficient elasticity is high. The water price that must be spend by the rice farmer by value of marginal product analysis is Rp 358.515/ha/season. The irrigation trouble that facing the farmer is irrigation way damage, garbage that obstruct water flowing, crab pest that discourage water in rice field, and the river damage that obstruct water flowing. The result of this study leads to the following recommendations. Firstly, the irrigation trouble must be fixed by the all subak member in united without expecting help from other stakeholder. Secondly, in the applying trouble fixing need a cost. The cost can be taken by implementation of the real water price by value Rp 358.515/ha/season. Keywords: rice, water price, co-efficient elasticity, irrigation trouble.